Jual Beli HP Tidak Ada Layanan Jaringan di Angkola Muaratais Tapanuli Selatan Perspektif Wahbah Az-Zuhaili - Nurmadani Nurmadani; Muhammad Amar Adly (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Buying and selling is a legal act that has existed since the existence of human civilization. In connection with the sale and purchase of mobile phones, there are often undue events where the seller is not responsible for the implementation of khiyar aib, this is experienced by consumers in buying and selling mobile phones with obstacles to no cellular network services due to illegal IMEI, duplication of IMEI and the use of temporary IMEI. If the IMEI of the cellphone is not officially registered, one day it may be subject to restrictions on the use of cellular network services. Meanwhile, when asked for accountability, the seller did not respond to consumer complaints, because the seller claimed to have tried the goods before handing over to the buyer. The research method used in this research is qualitative field research, the authors will reveal the meaning of the behavior and reality of the surrounding community. Primary data is a source of data that is directly obtained from the first source, namely people who buy unofficial cellphones at the counter. Secondary data is data obtained indirectly from data sources, secondary data in this study is data derived from literature (library research), namely research by examining and reading books or books, articles, and websites related to khiyar aib.